USER EXPERIENCE USING PRADITA DIGITAL LMS IN BLENDED LEARNING: A CASE STUDY IN PRADITA UNIVERSITY - Pratama , Arif; Radiegtya, Ega Wachid; Indrajit, Richardus Eko; Muh. Masri Sari (Jurnal Teknik Informatika (Jutif), 2023)
This research aims to evaluate user experience (UX) in using Pradita Digital Learning Management System (LMS) in Blended Learning process. In the current educational context, the use of LMS and online applications has become common, so it is important to conduct an evaluation to measure the level of satisfaction and effectiveness of using Pradita Digital LMS in the learning process. The method used in this research is A Technique for User eXperience Evaluation in e-Learning (TUXEL) Version 2.0. TUXEL method is a technique that allows researchers to evaluate usability and user experience when using a system. The research results are divided into three aspects, namely general usability, pedagogical usability, and UX. The questionnaire results show that the use of Pradita Digital LMS gets a good and agreeable response from the users in the learning process because the system is more interactive and interesting. Although Pradita Digital LMS still has shortcomings in general usability and pedagogical usability aspects, it has creative and innovative value for users in the learning process. Overall, the result of this research is that Pradita Digital LMS has creative and innovative value, although there are still shortcomings in the aspects of general usability and pedagogical usability. Even so, Pradita Digital LMS is able to provide a good user experience in the learning process. It is hoped that the results of this study can be input for the development of Pradita Digital LMS so that it can continue to be improved in terms of usability and user satisfaction, so that the online learning experience can be even better in the future.